344 Evaluation of Supplementation of Potassium Chloride and Choline Chloride in High Feed Grade Amino Acid Finishing Diets. (10th April 2018) - Ochoa, L; Graham, A; Greiner, L; Knopf, B; Goncalves, M A D; Cast, W; Orlando, U A D
Abstract: One thousand one hundred and ninety-one PIC (337 X Camborough) barrows and gilts were used to determine the impact of adding potassium chloride and choline chloride to diets containing high feed grade amino acids. Prior to the start of the study, pigs were fed a basal diet that contained 1.35% SID lysine for three weeks. At the start of the study, the pigs averaged 31.0 kg. Pigs were sorted by gender and placed into blocks with 23-25 pigs per pen. Blocks were set for the 4 treatments (0.15% L-lysine HCl, 0.35% L-Lysine HCl, 0.55% L-Lysine HCl, and 0.55% L-Lysine HCl+0.2% potassium chloride+0.05% choline chloride) within gender of similar weights with the block. The diets consisted of corn, soybean meal and dried distiller's grains and were balanced for SID lysine and SID Lys:ME. All other nutrients met or exceeded NRC (2012) and PIC (2016) recommendations. Pen weights and feed intake information were collected at the start and end of the phase to allow for calculation of average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (G/F). All pigs were vaccinated against porcine circovirus, Mycoplasma hyopneumoniae, Salmonella, and Lawsonia. The pigs were porcine reproductive respiratory syndrome and porcine epidemic diarrhea virus negative. Data were analyzed as a randomized complete block design using the PROC MIXED procedure of SAS with pen as the experimental unit, treatment as a fixed effect, and block as the random effect. Results were considered significant at P ≤ 0.05 and considered a trend at P > 0.05 and P ≤ 0.10. Overall, there were no significant differences in average daily gain (0.96, 0.98, 0.98, and 0.97 kg/d; P >0.10) or feed to gain (0.38, 0.39, 0.39, 0.39; P >0.10) between dietary treatments. In conclusion, the feeding of high levels of feed grade lysine when crude protein remains above 13% crude protein does not impact performance. Furthermore, the addition of potassium chloride and choline chloride did not influence performance.